IMPLEMENTASI HIGHER ORDER THINKING SKILLS TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK DALAM PEMBELAJARAN - Indah Suciati (Program Studi Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Institut Agama Islam Negeri (IAIN) Palu, 2022)
This study aims to describe the implementation of HOTS on students' critical thinking skills in learning. The method used is Systematic Literature Review with the PRISMA Model which consists of identification, screening, feasibility, and inclusion steps. Literature collection was carried out through the Google Scholar database and National Library within the 2020-2022 period to obtain 190 pieces of literature. After selection, 20 pieces of literature were analyzed using the Miles & Huberman interactive model consisting of information collection, reduction, data presentation, and conclusions. Thematic analysis is also used to answer predefined review questions. The findings show that the implementation of HOTS in learning is influential, positively correlated, efficient, and able to improve students' critical thinking skills. Not only that, the level of students' mathematical abilities in solving HOTS problems affects their critical thinking skills. There is also the implementation of HOTS that can be applied through instruments, teaching materials, assessments, or learning models. However, the challenges faced in the implementation of HOTS can be in the form of 1) low mathematical ability, 2) students who are not accustomed to working on HOTS questions, 3) interpretation in reviewing information is still low, 4) does not master the topic or material, and 5) less careful